(3HjGf eTcd CMGOjK QShd Gddg Udi Gddg Ydjg hSdes - (3GdWMGhj , CHh LYaQ,J (B321 (3g` s ((3CMeO Hf eMeO Hf efUhQ Hf gGTe GdTgjQ HGdahi s)
(3ChdgG (B:s
(3jHOC HHGH eG bO Qhi Yf QShd Gddg Udi Gddg Ydjg hSde ai CTO GdfGS YPGHkG jhe GdbjGeI s
(3BNQgG (B:s
(3jfJgi HHGH HjGf eTcd eG Qhi Yf QShd Gddg Udi Gddg Ydjg hSde ai bhdg ai GdUdGI Ydi GdejJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3QhGjI s
Keywords: (3GdMOjK h GdeUWdMs